1988
DOI: 10.1177/107110078800800607
|View full text |Cite
|
Sign up to set email alerts
|

Foot Pressure Studies in the Assessment of Forefoot Arthroplasty in the Rheumatoid Foot

Abstract: To assess the results of forefoot arthroplasty, dynamic and static foot pressure studies have been made of the rheumatoid foot in both a prospective study group of 60 feet and in a retrospective study group of 18 feet. Significant reductions of pressure in the forefoot were found. Problems associated with the first and fifth metatarsals were considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…These results have been confirmed by several authors [2,20,21]. As a result Tillmann [22] suggested that Keller's operation should not be combined with a metatarsal head resection of the lesser toes.…”
Section: Discussionsupporting
confidence: 75%
“…These results have been confirmed by several authors [2,20,21]. As a result Tillmann [22] suggested that Keller's operation should not be combined with a metatarsal head resection of the lesser toes.…”
Section: Discussionsupporting
confidence: 75%
“…Seven reports of 4 prospective observational studies were identified. These evaluated minor surgery (plantar callous debridement) (25), intraarticular radiation to the ankle (26), forefoot arthroplasty involving the great toe (4 reports of the same patient group with different followup times and outcome measures) (27)(28)(29)(30), and first MTP joint silicone implantation (31). Almost all studies, apart from the study on intraarticular radiation, involved only the forefoot.…”
Section: Review Of Foot Disease Interventions In Ramentioning
confidence: 99%
“…Larger groups of patients, evaluated postoperatively, showed better clinical results; at a mean of 3 years after surgery, 91% of 35 patients were satisfied (29) and at a mean of 4 years, 89% of 28 patients were satisfied and 75% noted painless walking (28). A study examining static and dynamic foot pressures at a mean of 2 years after surgery (30) showed that such surgery led to a marked reduction of pressure under the central metatarsals.…”
mentioning
confidence: 99%
“…Betts et al 4 and Stockley et al 4,21,24 presented quantitative data to show a reduction in plantar pressure during walking. This was under the middle forefoot regions (MTHs 2, 3, and 4) in a prospective study of 60 feet in patients with RA who had undergone a modified panmetatarsal head resection.…”
Section: Discussionmentioning
confidence: 99%
“…Several surgical techniques have been proposed to accomplish the presumed goal of metatarsal head load relief in such patients. 4,1014,16,17 Results reported have mostly been subjective in nature. 1,3,8,26 It is notable that in one study 25 almost one third of the patients complained of pain and callosities at 5 years, which suggests that elevated plantar pressures continued to exist in those cases.…”
Section: Discussionmentioning
confidence: 99%